Desafio imune neonatal com lipopolissacarídeo desencadeia alterações comportamentais e imunológicas/neurotróficas duradouras relacionadas ao sexo e a idade em camundongos : relevância para o transtorno do espectro autista (TEA) - Custódio, Charllyany Sabino (2017)
Early life adversities, such as infections and stress, are related to the manifestation of neuropsychiatric disorders, such as autism and schizophrenia. These changes may be triggered by inflammatory and / or neurotrophic mechanisms. In this context, we decided to carry out a wide range of behavioral and neurobiological tests, such as the participation of indolamine 2,3-dioxygenase (IDO) - the first tryptophan degradation enzyme that limits the speed in the kynurenine pathway, associated with a decrease in serotonin And interleukins, oxidative stress, and other neurochemical markers relevant to the study in male and female swiss mice (postnatal day (PN) 35) and neonatal challenged adults (PN70) (PN 5 and 7) with Lipopolysaccharide (LPS) of the strain Escherichia coli, with the purpose of contributing to the determination of the so-called critical periods of development, making it possible in the future to prevent and treat changes in the most harmful periods, Quality of life for the patient, family and society, as well as the reduction in Gies triggered by LPS exposure during neurodevelopment. Since neurodevelopmental disorders are influenced by sex, we evaluated male and female mice. Male mice challenged with LPS showed type-depressive behavior, anxiety, repetitive behavior and working memory deficits in the PN35, whereas in PN70 only the anxiety and depressive-type behaviors were maintained. Females had pre-pulse inhibition (PPI) deficits at both ages studied. Neurochemical changes were determined in the prefrontal cortex (CPF), hippocampus (HC) and hypothalamus (HT). We observed increased interleukin (IL-4) (PFC, HC and HT) and decreased levels of IL-6 (PFC, HC and HT). There was an increase in brain-derived neurotrophic factor (BDNF) (HC) in both sexes and ages evaluated. Only male mice challenged with LPS showed increased myeloperoxidase (MPO) activity in HC in adolescence and adulthood and increased levels of interferon gamma (IFNγ), nitrite, IDO expression, and parvalbumin decrease in adult. In the kinurenin pathway, serotonin (5-HT) (HC) decreased only in male mice, whereas quinolinic acid (QUIN) decreased in both sexes in PN70. Together, these were the main behavioral and neurochemical differences observed in the present study between males and females who underwent neonatal immune challenge by LPS. We conclude that the challenge for neonatal LPS triggers a spectrum of neurobiological behaviors and changes that occur during adolescence and resemble non - specific (atypical) autistic spectrum disorder, possibly being a relevant model for the study of the differences of this disorder.